Optimising processing and sensory characteristics of Bean Blue : a blue mould tofu - Näsholm, Martina (SLU/Department of Molecular Sciences, 2018)
The increase in the global population leads to increased demand for food and espe-cially protein sources. Legumes have potential to support the increased worldwide demand for protein. Faba bean is a legume with high protein content which can be grown in Sweden. Bean Blue is a blue mould tofu based on faba bean that has been developed by researchers at the Swedish University of Agricultural Sciences (SLU) and the Research Institutes of Sweden (RISE). The purpose of this master thesis was to optimise the processing steps and the sensory characteristics of the final product by altering different parameters. The development of Bean Blue was divided into technical and sensory trials. The result from the technical trials was evaluated during production and by sensory evaluation of the final product by the development team. The sensory trials were evaluated through both consumer- and description tests. The results showed that the water:bean ratio during processing could be decreased from 9:1 to 4:1. The original method that included the use of 70 % faba bean and 30 % soybean could be replaced by a new method including the use of 100 % faba bean and removal of the starch. The original homofermentative starter culture could not be replaced by a heterofermentative starter culture due to poor mould growth and no pore formation. Rapeseed oil could replace cooking oil without any changes in the sensory quality. The process of Bean Blue was optimised by decreasing the wa-ter:bean ratio, which enhanced handling of the bean milk during pressing to remove okara (bean solids), and shortened draining time. The sensory quality was improved and the final product was described as more creamy and less beany in taste compared with the starting recipe. All parameters together have led to a more advantageous product from an environmental point of view (usage of 100 % faba, and Swedish rapeseed oil) without negative effect on the sensory properties.